Evacuation of Delayed Packets in Networks - Sriee S.K.M, Vidhiya Madhu; S, Nandhini. (IJRDO -Journal of Computer Science Engineering, 2017)
The aim of this paper is to give idea ofpostponed packets in networks. At presentthe networks which we are using supportsonly two classes of traffic, it takes long timeto service if there is any failure. Hence tosolve all these problems a OCGRRtechnology has been developed. This is theadvanced version of OCRR technology. Itrequires a processor of 500MHZ and above,ram of 128 mb and hard disk of 10 gb size.It makes use of jdk 1.5, windows 2000server family operating system and sqlserver databases. In OCGRR, small roundsof a frame and a packet-by- packet are madeused such that every stream inside a classcan send only one packet in each smallround. .In this packets of same class aresent to the destination. Before frame isscheduled, each output port data streams arestored in a separate Buffer .Buffers areplaced in frames such that each frameconsists of only one buffer. OnceScheduling is done transmission trafficoccurs and data is transferred according to